Analisis Kesulitan Siswa Dalam Menyelesaikan Soal-soal Segitiga Setelah Pembelajaran Kooperatif : (Studi Kasus Siswa SMP Tamansiswa Diski) - Meman Marpaung (Institute of Computer Science (IOCS), 2021)
The problem in this study is: How to describe the difficulty of students working on triangular problems after the provision of cooperative learning. The goal to be achieved in this study is: getting an overview of the difficulty of students working on triangular problems after the provision of cooperative learning to tamansiswa Diski junior high school students. The population in this study is a student of class VII Tamansiswa Diski Junior High School who is actively enrolled which numbers 148 people. The determination of the sample of authors was done in a random way as many as 30 people taken from class VII students. The data collection tool used in this study is: The test that provides mathematical problems about the triangle as much as 10 points of the test form problem is an